(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2021)
The area planted with Gmelina arborea (melina) in Ecuador has increased in the last decade, currently this forest species is affected by the disease "vascular wilt and stem rot", which is killing thousands of trees in the country. Ceratocystis fimbriata is listed as the causative agent of the disease, However, the complex symptoms and the frequent isolation of Fusarium spp. from diseased trees, make us suspect that this phytopathogen is involved in the pathogenesis of melina. Koch’s Postulates were applied at the greenhouse level, and for the effect, 5 treatments based on the inoculation of 17 G. arborea plants of 4-month-old per treatment were plated. T1 = Fusarium sp.1, T2 = Fusarium sp.2, T3 = Fusarium sp.3, T4 = Fusarium sp.4, and T5 = agar-agar (control). A complete randomized design (CRD) was used and the plants were evaluated 155 days after inoculation. The treatments Fusarium sp.1 and Fusarium sp.2 caused the largest apparent volumes of necrosis (2.31 cm3 and 2.43 cm3), and generated mild symptoms of disease, however they did not die, so these results cannot be considered conclusive yet. It is necessary to continue investigating the role of Fusarium spp. in the pathogenesis of melina.